2012
DOI: 10.1037/a0026988
|View full text |Cite
|
Sign up to set email alerts
|

The role of attention for context–context binding of intrinsic and extrinsic features.

Abstract: There is converging evidence that the feeling of conscious recollection is usually accompanied by the bound retrieval of context features of the encoding episode (e.g., Meiser, Sattler, & Weiβer, 2008). Recently, however, important limiting conditions have been identified for the binding between context features in memory. For example, focusing on the semantics of the stimuli during encoding eliminates binding between perceptual context features (Meiser & Sattler, 2007). In the present research, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 18 publications
3
38
2
Order By: Relevance
“…But it does make one pause to consider how our traditional paradigms (e.g., Meiser & Br€ oder, 2002;Starns & Hicks, 2005) often downplay low-level perceptual encoding of objects and of their features that surely must occur in order to perceive an object as that particular object, as opposed to further binding and its residual effects that are caused by various encoding or retrieval processes operating on those representations. An exception here is the work by Boywitt and Meiser (2012b) showing that stochastic dependence was greater in multidimensional source memory for features intrinsic to item presentation as opposed to extrinsic (Experiment 1), but that even extrinsic features showed dependence when people were told to focus on both features during encoding (Experiment 2). Their work represents an attempt to manipulate context features that might be more or less inherently associated with item/object information.…”
Section: Related Work In Object Recognition Using Multidimensional Pamentioning
confidence: 79%
See 2 more Smart Citations
“…But it does make one pause to consider how our traditional paradigms (e.g., Meiser & Br€ oder, 2002;Starns & Hicks, 2005) often downplay low-level perceptual encoding of objects and of their features that surely must occur in order to perceive an object as that particular object, as opposed to further binding and its residual effects that are caused by various encoding or retrieval processes operating on those representations. An exception here is the work by Boywitt and Meiser (2012b) showing that stochastic dependence was greater in multidimensional source memory for features intrinsic to item presentation as opposed to extrinsic (Experiment 1), but that even extrinsic features showed dependence when people were told to focus on both features during encoding (Experiment 2). Their work represents an attempt to manipulate context features that might be more or less inherently associated with item/object information.…”
Section: Related Work In Object Recognition Using Multidimensional Pamentioning
confidence: 79%
“…However, extrinsic contexts were successfully integrated in a second experiment following an explicit instruction to associate the color and locations of the squares with the centrally presented words. Boywitt and Meiser (2012b) demonstrated further that the two source dimensions must be presented concurrently with item presentation at encoding in order for the stochastic dependence to occur. They compared conditions in which the two source dimensions were presented together, with word color and position evident in a single presentation, versus a condition in which color was evident in one presentation and then position manipulated in a separate presentation.…”
Section: Relationship Of Stochastic Dependence To Attentional Resourcesmentioning
confidence: 96%
See 1 more Smart Citation
“…Although we do not distinguish between the two types of source information in the current study, future research should examine the recovery of contextual information in the absence of item memory for intrinsic versus extrinsic source details, as they likely differ in their relative contribution of encoding and retrieval processes needed for information to be bound into or reactivated from memory (e.g., Boywitt & Meiser, 2012). For example, it has been suggested that whereas intrinsic source features are bound relatively automati cally to item information and promote familiarity-based retrieval processes, extrinsic source details require more effortful process ing to form an associative link between the item and source and promote recollective retrieval processes (Ecker et al, 2007b).…”
Section: Discussionmentioning
confidence: 94%
“…Many studies have shown that extrinsic and intrinsic context information are differently processed and represented in memory. For example, Mulligan ( 2011 ) and Nieznaski ( 2012 , 2014 ) have demonstrated that generating an item results in an increase in memory for extrinsic context but a decrease in memory for intrinsic context (see Boywitt & Meiser, 2012 ; Ecker, Maybery, & Zimmer, 2013 ; Ecker, Zimmer, & Groh-Bordin, 2007 ; Geiselman & Bjork, 1980 ; Godden & Baddeley, 1980 ; Troyer & Craik, 2000 ; for studies showing differential consequences of processing intrinsic vs. extrinsic context). The explanation why expectancy effects seem to be different for extrinsic versus intrinsic contexts needs future experimental investigation.…”
Section: Discussionmentioning
confidence: 99%